2024
DOI: 10.5114/biolsport.2024.127384
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of short vs. long-distance sprint training on sprinting and agility performance in young soccer players

Ezequiel Rey,
Samuel Carrera,
Alexis Padrón-Cabo
et al.

Abstract: The purpose of this study was to examine the effects of short sprint-distance training (SST) compared with long sprint-distance training (LST), matched for the total session training volume, on short-, medium- and long-distance sprint performance and agility in young soccer players. Eighteen U19 male players (age: 17.1 ± 0.7 years; height: 178.0 ± 6.3 cm, body mass: 69.4 ± 6.6 kg) were randomly assigned to SST ( n = 9) or LST ( n = 9) group. The intervention progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The implementation of SEST covers a sprint distance of 160 meters multiplied by 6 sets, where this model has the Long Sprint Training category. In previous research, Rey et al (2024) reported that Short Sprint Training (SST) and Long Sprint Training (LST) were effective in improving performance measures specific to soccer. However, LST had a better percentage of improvement, with analysis showing significant improvement in 5 m, 10 m, 20 m, 30 m and 40 m sprint.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of SEST covers a sprint distance of 160 meters multiplied by 6 sets, where this model has the Long Sprint Training category. In previous research, Rey et al (2024) reported that Short Sprint Training (SST) and Long Sprint Training (LST) were effective in improving performance measures specific to soccer. However, LST had a better percentage of improvement, with analysis showing significant improvement in 5 m, 10 m, 20 m, 30 m and 40 m sprint.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, soccer players must develop their running ability, especially within 20 meters, to optimize their running speed in various game situations, contributing to team success and individual achievements (Nicholson et al, 2022). According to the opinions of Rey et al (2024) suggests that short-distance running exercises can improve sprint performance and turning speed. In addition, to evaluate players' physical abilities, a running speed of 20 meters is one of the parameters used (Altmann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%